The investor decision in managing risk during pre and post global financial crisis in Malaysia / Fati Hah Najihah Nadzar - Nadzar, Fati Hah Najihah (Faculty of Business and Management, 2017)
Global financial crisis has given enormous impact for the world's economy. During the global financial crisis began in United States (U.S), many large financial institutions have been fall out and negatively affected world's economy. The most affected industry is the banking industry and world's stock market. Malaysia is one of the countries that received an impact due to global financial crisis of 2007/2008 (Angabini & Wasiuzzaman, 2011). This research comes from the investor decision in managing risk during pre and post global financial crisis in Malaysia that lead to the existence of flight-to-quality from stock to bonds market. In the Princeton Encyclopedia of the World Economy, Aizenman (2009) describes flight-to-quality as actions by the investors to "liquidate assets in financial institutions due to a sudden increase in their perceived risk." When stock-bond correlations are positive during pre-crisis, and turn to negative during crisis, there is flight to quality (Baur & Lucey, 2009). Hence, the purpose of this study is to investigate the existence of flight from stock market to bond market which is before crisis, during crisis and after crisis in Malaysia. The sample of this study is the weekly stock indices and bond indices consist from July 2007 until July 2017. The method apply in this research is event study and uses to measure the effect of an event on the stock and bond value.